Physical, Chemical, and Biological Maturity Parameters of Fish Waste Bokashi - Ikhsan Hasibuan; Prihanani Prihanani; Meylinda Puspitasari (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2021)
Indonesia is the second greatest fish producer in the world after China with a total production of almost seven million tonnes in 2018. Meanwhile, Bengkulu is one of the provinces that are rich in fish resources. However, about 30-60% of fish produced is considered fish waste. Ikan rucah is small fish that has low or no economical value, thus it is regarded as a waste. Ikan rucah should be managed to avoid its negative effects on the environment. One of the options is by transforming it into organic fertilizer. Nevertheless, producing organic fertilizer by using fish waste is complicated since it will be easily rotten in futile fermentation. Thus, the objective of the research was aimed to evaluate the maturity of fish waste bokashi by using three parameters including physical, chemical, and biological aspects. The study had been carried out in the Laboratory of Agrotechnology, Faculty of Agriculture, University of Hazairin, Bengkulu in late 2020. The research was begun by preparing fish waste in three drying levels that were 85%, 70%, and 30% water content thus they were stated as fresh, medium, and dry fish waste, respectively. Each of those was then fermented in anaerobic methods for 2 and 3 weeks. The bokashi produced then analyzed in the physical, chemical, and biological characteristics. The results of this study confirmed that ikan rucah could be used as a source of organic material for organic fertilizer. Every treatment tested showed a good maturity level in physical parameters. Furthermore, the important findings were the high contents of main nutrients that were 1.5-5% and 4-5%, respectively for nitrogen and phosphorus. In addition, the biological maturity reached after 3 weeks of fermentation that confirmed germination index (GI) of about more than 100% or categorized as highly mature.